Multivariable Chain Rule – Proving an equation of partial derivatives – Exercise 6498

Exercise

Given the differentiable function

z=yf(x2y2)z=\frac{y}{f(x^2-y^2)}

Prove the equation

1xzx+1yzy=zy2\frac{1}{x}\cdot z'_x+\frac{1}{y}\cdot z'_y=\frac{z}{y^2}

Proof

Define

u=x2y2u=x^2-y^2

We get the function

z=yf(u)=yfz=\frac{y}{f(u)}=\frac{y}{f}

And the internal function

u(x,y)=x2y2u(x,y)=x^2-y^2

We will use the chain rule to calculate the partial derivatives of z.

zx=zffuux=z'_x=z'_f\cdot f'_u\cdot u'_x=

=y1f2(u)fu2x==y\cdot \frac{-1}{f^2(u)}\cdot f'_u\cdot 2x=

=2xyfuf2(u)=\frac{-2xyf'_u}{f^2(u)}

 

zy=1f(u)yfuuyf2(u)=z'_y=\frac{1\cdot f(u)-y\cdot f'_u\cdot u'_y}{f^2(u)}=

=1f(u)+2y2fuf2(u)=\frac{1}{f(u)}+\frac{2y^2f'_u}{f^2(u)}

We will put the partial derivatives in the left side of the equation we need to prove.

1xzx+1yzy=\frac{1}{x}\cdot z'_x+\frac{1}{y}\cdot z'_y=

=1x2xyfuf2(u)+1y(1f(u)+2y2fuf2(u))==\frac{1}{x}\cdot \frac{-2xyf'_u}{f^2(u)}+\frac{1}{y}\cdot (\frac{1}{f(u)}+\frac{2y^2f'_u}{f^2(u)})=

=2yfuf2(u)+1yf(u)+2yfuf2(u)==\frac{-2yf'_u}{f^2(u)}+\frac{1}{yf(u)}+\frac{2yf'_u}{f^2(u)}=

=1yf(u)=\frac{1}{yf(u)}

Now, we will put the partial derivatives in the right side of the equation we need to prove.

zy2=yf(u)y2=\frac{z}{y^2}=\frac{\frac{y}{f(u)}}{y^2}=

=yf(u)1y2=1yf(u)=\frac{y}{f(u)}\cdot\frac{1}{y^2}=\frac{1}{yf(u)}

We got the same result in both sides as required.

Have a question? Found a mistake? – Write a comment below!
Was it helpful? You can buy me a cup of coffee here, which will make me very happy and will help me upload more solutions! 

Share with Friends

Leave a Reply